The Impact of Human Resource Planning and Development on The Productivity of SMEs in The Bulak District of Surabaya During The Covid-19 Pandemic - Yulia Kartikaningrum (Journal Research of Social Science, Economics, and Management, 2026)
In this era of the industrial revolution 4.0, human resources are required to be more sophisticated and advanced in all fields. The internet and technology continue to be put forward in welcoming every effort and activity against globalization. The following research aims to find out and analyze the influence of human resource planning and development on the productivity of MSMEs in Bulak Sub-district Surabaya during the Covid-19 Pandemic. The following study used a quantitative approach and the analysis method uses multiple linear regression. The data collection technique in this study used a questionnaire with a sample of 90 respondents. The results of the following study show that planning has a significant effect on productivity due to the significance value of 0.000<0.05. Human resource development has a significant effect on productivity because of the significance value of 0.000<0.05. Simultaneous planning and human resource development has a significant effect on productivity due to the significance value of 0.000<0.05. Human resource planning and development affected the productivity variable by 63.1% and the remaining 36.9% was explained by other variables outside the model.